Analisis Kinerja Keuangan Perusahaan Menggunakan Metode Economic Value Added (EVA) Pada PT Semen Baturaja (Persero) Tbk. - Etri Angeraini; Sally Maria Bramana; Evandry Deswana (STIE DWI SAKTI BATURAJA, 2023)
Economic Value Added (EVA) is a method that can be used by PT Semen Baturaja (Persero) Tbk in measuring financial performance to determine whether the company has succeeded in creating added value or not every year. This study aims to analyze the company's financial performance using the Economic Value Added (EVA) method at PT Semen Baturaja (Persero) Tbk. 2017 – 2021. The method used in this study is a quantitative method with statistical calculations such as Net Operating After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost Of Capital (WACC), and Economic Value Added (EVA). The results of this study indicate that the value of Economic Value Added (EVA) at PT Semen Baturaja (Persero) Tbk. > 0 which means the company has created added value for the company, even though the EVA value has increased and decreased every year.